Expression Profiling and Population Structure Analysis of Copy Number Variants (CNVs) in Autism Spectrum Disorder (ASD): 1st Triennium Post Doc Fellowship Report - Pires Carreira da Conceição, Inês Susana (2014)
Fellowship: SFRH/BPD/74739/2010